Research directions and opportunites supporting the spread of agriculture digitalisation - Nátz, Katalin; Véghné Kohut, Dorottya; Szalay Zsigmond, Gábor (Studia Mundi – Economica, 2022)
Without digitalisation and automation, it is not possible to gain a competitive advantage in the current market situation, and this is also true for agriculture. Technological developments make it possible to use methods, machines, precision tools and processes in agriculture that reduce production costs and the negative impact on the environment. By reducing costs, farmers will be able to increase production, despite the fact that the labor market is struggling with a lack of resources, which is also true for agriculture. For emerging challenges such as climate change, stringent food and nutrition security standards and changing consumer needs can be addressed by seizing the opportunities offered by technology. To do this, farmers need ready-made solutions based on exponentially generated data. The data needs to be made available to producers in the form of services, thus supporting more efficient decision-making. This solution can also exist in framework of community realization, where there is more trust within the farming community, as againts to technological solutions implemented from the outside from the top down. It is not enough to create the right data environment and usable service, but it is also important to bridge the generation gap and low digital literacy problems. To do this, however, it is essential to create a non-profit data environment that collects data from the digital tools used in the business value chain and then makes it available to farmers in the form of services. This will help you make better management decisions. Holistic and open system thinking is essential for success and sustainable agriculture.